Theory of mind and the development of communication: the analysis of experience - Garaffo, Teresa (Formazione & insegnamento, 2015)
Recent studies have highlighted the importance of metacognition for the development of skilled learning abilities. In this paper the author focusses on a crucial component of metacognition: the analysis of experience, as it is performed through verbal thought. The origins of this cognitive operation are found in the attention that very early infants devote to the structure of intentional action. Afterwards, intersubjective dialogue profoundly changes the nature of the operation, by transferring it to a more explicit level. Implications for education are considered.